Análise de métodos de produção de interfaces visuais para recuperação da informação - Xavier, Raphael Figueiredo [UNESP] (Universidade Estadual Paulista (Unesp), 2009)
The advent of the Web and the consequent increase in the volume of electronic information had caused many problems about access, search, location and retrieval of information in large volumes of data. This work is a revision of the different models, methods and algorithms to create interfaces for Visual Information Retrieval, classified according to their production process: Analysis and Data Processing, Implementation of algorithms for classification and distribution of Visual and Application Processing Techniques of Visual. The results of other researchers want to serve as a tool for the election of one or another combination methodology in the development of specific proposals for visual interfaces for information retrieval, and suggest the need for more research into new techniques for processing visual.

O advento da Web e o conseqüente aumento no volume de informações eletrônicas acarretaram muitos problemas em relação ao acesso, busca, localização e recuperação de informação em grandes volumes de dados. O presente trabalho realiza uma revisão dos diferentes modelos, métodos e algoritmos existentes para a geração de Interfaces Visuais para Recuperação da Informação, classificados segundo ao seu processo de produção: Análise e Transformação dos Dados, Aplicação de Algoritmos de Classificação e Distribuição Visual e Aplicação de Técnicas de Transformação Visual. Os resultados pretendem servir a outros investigadores como ferramenta para a eleição de uma ou outra combinação metodológica no desenvolvimento de propostas específicas de Interfaces Visuais para Recuperação da Informação, além de sugerir a necessidade de maiores investigações sobre novas técnicas de transformação visual.
Keywords: Recuperação da informação; Interfaces (Computadores); Recuperação da informação - Interfaces visuais; Visualização da informação; Information Retrieval; Information Visualization; Visual Information Retrieval Interface